INTRODUCTION TO HUMAN PHYSIOLOGY FOR MEDICAL STUDENTS (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
With recent advances in the fielded of human physiology, it has become urgent to provide an up to date review in the subject of human physiology.This book to help medical student in understanding modern human physiology. It presents the whole subject in brief comprehensive and up to date form.I hope this book will be a real help to undergraduate medical students, as well as to postgraduate and candidates of higher degree, in the field of human physiology.